Preferential inhibition of plasmid replication in vivo by altered DNA gyrase activity in Escherichia coli. - Uhlin, B E (1985)
The thermosensitive growth phenotype exerted by runaway-mutant plasmids was suppressed by sublethal doses of the DNA gyrase inhibitors novobiocin or nalidixic acid, although the latter drug was less efficient. A novobiocin-resistant gyrB mutant Escherichia coli strain prevented expression of the runaway phenotype at 37 to 42 degrees C in the absence of any drug.